Exploration of supervisor and student experiences during master’s studies in a health science faculty - Chikte, UME; Chabilall, JA (South African Journal of Higher Education, 2016)
Significant growth in postgraduate student numbers with seemingly little change in staff composition and supervision capacity have prompted the need for research into the experiences of supervisors in a diverse interdisciplinary health sciences department. This article contends that supervision strategies form an important facet of institutional knowledge sharing in an interdisciplinary context especially in developing the capacity of postgraduate students to apply competencies later within the macro society in a sustainable manner. The article addresses one of the research questions of a larger study: What are the experiences of supervisors during the supervisory process of master’s students in a Health Science Faculty? Supervisors were of the view that they were committed to their supervision duties. Their multiple roles meant that they had to be encouraging, understanding, empathetic, set boundaries, be supportive while they act as guides and mentors who are expected to provide timeous and continuing feedback. To provide a comprehensive appreciation of the study, the article also presents significant findings from the qualitative component pertaining to student-views of the supervision process. Recommendations relate to the workload of supervisors, faculty development and greater access to resources including funding that would generally influence postgraduate supervision.